A high‐gain bow‐tie antenna with phase gradient metasurface lens. Issue 11 (29th July 2021) - Wang, Ziye; Yang, Zhengwei; Zeng, Weihua; Zhao, Xiao; Guo, Linyan; Guo, Minjie
Abstract: A high‐gain bow‐tie antenna with double‐layer phase‐gradient metasurface (PGMS) lens is proposed. A modified bow‐tie antenna is designed as a feed, which has end‐fire characteristics. The proposed PGMS can transform quasi‐spherical electromagnetic wave to plane wave within the frequency band from 1.7 to 2.1 GHz, thereby the proposed lens antenna has a good beam focusing effect. The measured gain is from 9.5 to 12.8 dBi and a −3 dB gain bandwidth of around 20% is achieved. At the same time, the gain increases 6.5 dB on average in the whole working frequency band. Simulated and measured results show that the designed modified bow‐tie antenna with PGMS lens has high gain and high directivity, which can well meet the requirement of microwave imaging system.